Popular Culture of Miss Beauty Pageant in Nepali Context - Kharel, Megh Prasad (Interdisciplinary Journal of Management and Social Sciences, 2021)
This study examines the Miss Beauty Pageant in the light of popular culture in Nepali context. In the first section, the research attempts to explore different causes of having popularity of Miss Pageant such as rapidly increasing of electronic media, emerging liberal consumer society, glamour politics of physical beauty of the female and gender identity. In the second section, the research discusses two phases of beauty pageant: national-wise and heterogeneous identities based wise (i.e. regional, University, ethnic, caste, professional and institutional wise). In the third section, the article also examines the causes of contradictory opinion from Marxist and feminist force on the contest of the Miss pageant as they underscore the political-cultural side of imperialism, gender discrimination and commercialization of female body, sex and beauty. Despite the opponent voice, the popularity of various beauty contests are increasing day by day. However, specific feature of the pop culture is that it does not distinguish the right and wrong in the overflow of the consumption of the cultural practices. Consequently, opponent circles like Marxists and feminists have almost failed to stop the beauty contest in the consumer mode of Nepali society in the present context.